Photo‐Induced Hydrogel Formation Based on g‐C3N4 Nanosheets with Self‐Cross‐Linked 3D Framework for UV Protection Application. Issue 1 (12th November 2018) - Ye, Boyong; Yao, Chengkai; Yan, Mengdie; Zhang, Huanhuan; Xi, Fengna; Liu, Jiyang; Li, Benxia; Dong, Xiaoping
Abstract: Composite hydrogels of graphitic carbon nitride nanosheets (CNNS) and polyacrylamide (PAM) with superior UV absorption and visible transparence capabilities are reported. CNNS is employed not only as a photocatalytic initiator to trigger the polymerization of acrylamide, but also as a cross‐linker to 3D connected PAM chains via hydrogen bonds. The obtained CNNS/PAM hydrogels are highly moldable for preparing various forms, and have good mechanical properties, self‐healing ability, and photo‐stability. Furthermore, the composite hydrogels have a wide spectral range for UV absorption compared to conventional UV protective materials. Besides the complete screening of UVB (280–315 nm) in sun radiation, the CNNS/PAM hydrogel film can also filter >95% UVA radiation (315–400 nm) by regulating the coating thickness, meanwhile retaining a high visible transmittance. Therefore, the CNNS/PAM hydrogels have potential applications for shielding UV radiation. Additionally, this strategy provides a common and facile route to fabricate functional composite hydrogels via photo‐induced polymerization. Abstract : Self‐cross‐linked carbon nitride nanosheets (CNNS)/polyacrylamide composite hydrogels are prepared via photocatalytically triggered polymerization, which have exceptional moldability, self‐healing properties, and photo‐stability. The 2D ultrathin structure and excellent optical property of CNNS endow this hydrogel with superior UV absorption and visible transmittance ability. It can completely shield UVB and >95% UVA in sun radiation, meanwhile preserving a highly visible transmittance.